Clinical Characteristics and Long-term Follow-up of Patients with Diabetes Due To PTF1A Enhancer Mutations - BEREKET, ABDULLAH; HALİLOĞLU, BELMA (My University, 2020)
Abstract Context Biallelic mutations in the PTF1A enhancer are the commonest cause of isolated pancreatic agenesis. These patients do not have severe neurological features associated with loss-of-function PTF1A mutations. Their clinical phenotype and disease progression have not been well characterized. Objective To evaluate phenotype and genotype characteristics and long-term follow-up of patients with PTF1A enhancer mutations. Setting Twelve tertiary pediatric endocrine referral centers. Patients Thirty patients with diabetes caused by PTF1A enhancer mutations. Median follow-up duration was 4 years. Main Outcome Measures Presenting and follow-up clinical (birthweight, gestational age, symptoms, auxology) and biochemical (pancreatic endocrine and exocrine functions, liver function, glycated hemoglobin) characteristics, pancreas imaging, and genetic analysis. Results Five different homozygous mutations affecting conserved nucleotides in the PTF1A distal enhancer were identified. The commonest was the Chr10:g.23508437A>G mutation (n = 18). Two patients were homozygous for the novel Chr10:g.23508336A>G mutation. Birthweight was often low (median SDS = –3.4). The majority of patients presented with diabetes soon after birth (median age of diagnosis: 5 days). Only 2/30 presented after 6 months of age. All patients had exocrine pancreatic insufficiency. Five had developmental delay (4 mild) on long-term follow-up. Previously undescribed common features in our cohort were transiently elevated ferritin level (n = 12/12 tested), anemia (19/25), and cholestasis (14/24). Postnatal growth was impaired (median height SDS: –2.35, median BMI SDS: –0.52 SDS) with 20/29 (69%) cases having growth retardation. Conclusion We report the largest series of patients with diabetes caused by PTF1A enhancer mutations. Our results expand the disease phenotype, identifying recurrent extrapancreatic features which likely reflect long-term intestinal malabsorption.